2017
DOI: 10.1371/journal.pone.0189612
|View full text |Cite
|
Sign up to set email alerts
|

Immunodominant cytomegalovirus-specific CD8+ T-cell responses in sub-Saharan African populations

Abstract: More than 90% of children in Africa are infected with cytomegalovirus (CMV) by the age of 12 months. However, the high-frequency, immunodominant CD8+ T-cell responses that control CMV infection have not been well studied in African populations. We therefore sought to define the immunodominant CMV-specific CD8+ T-cell responses within sub-Saharan African study subjects. Among 257 subjects, we determined the CD8+ T-cell responses to overlapping peptides spanning three of the most immunogenic CMV proteins, pp65, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…The unusual magnitude of the HLA-B * 44:03-restricted NW8-specific CD8+ T cell response deserves comment. In most individuals, >3% of CD8+ T cells, and in one individual almost 1 in 5 CD8+ T cells (19%), are specific for this single response ( 22 ). Even by the standards of CMV-specific CD8+ T cell responses, which are renowned to be very large, this is an exceptional example.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The unusual magnitude of the HLA-B * 44:03-restricted NW8-specific CD8+ T cell response deserves comment. In most individuals, >3% of CD8+ T cells, and in one individual almost 1 in 5 CD8+ T cells (19%), are specific for this single response ( 22 ). Even by the standards of CMV-specific CD8+ T cell responses, which are renowned to be very large, this is an exceptional example.…”
Section: Discussionmentioning
confidence: 99%
“…We recently characterised an immunodominant CMV-specific response in African populations that is restricted by HLA-B * 44:03 ( 22 ). This class I molecule is expressed in ~15% of African populations ( 23 ) and differs by a single amino acid from the closely related HLA-B * 44:02 ( 24 ), the most prevalent HLA-B * 44 subtype in Caucasian populations.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, this increasing inequality in clone sizes is thought to have functional consequences, which effectively translate to increased susceptibility to infectious disease (14). We recently described a paragon of virally-induced TCR repertoire distortion by showing that CMV-infected HLA-B * 44:03 individuals possessed large oligo/monoclonal expansions of superdominant clones (25,26). Thus, in this setting, the immunological space available to tackle pathogens other than CMV may be significantly compromised by the extent of such TCR repertoire skewing (27).…”
Section: Introductionmentioning
confidence: 99%
“…We previously showed that HLA-B * 44:03 subjects mounted a robust CD8 T cell response against the immediate-early-2 (IE-2)derived epitope NEGVKAAW (NW8) (25), with drastic clonal expansion of superdominant TCR clonotypes (26). This finding led us to the hypothesis that TCR superdominance may be a feature of "memory inflation" occurring as a result of gradual expansion of antigen-specific T cells over time.…”
Section: Introductionmentioning
confidence: 99%
“…HIT appears to augment IFN-γ secretion, especially in the case of circulating memory VSTs with low precursor frequencies, like AdV-specific T cells [46]. Conversely, T cells against the highly immunodominant antigen CMV pp65 [54], which have higher frequencies in the circulation of healthy donors, did not respond as much to exercise. This finding suggests that HIT is most beneficial for boosting antigen-specific T cells with low precursor frequencies.…”
Section: Discussionmentioning
confidence: 95%